Whose Fundamental Constitutions? Locke, Slavery, and Manuscript Evidence - Brewer, Holly (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2024)
This article uses the methods that Locke advocated in his Essay Concerning Human Understanding to evaluate manuscript evidence from five different schemes and two drafts of the Fundamental Constitutions of Carolina, to thereby determine what role, if any, John Locke had in writing it, and in advocating for slavery and absolutism. It focuses on the influential claims put forward by David Armitage 20 years ago, that Locke was responsible for actively promoting slavery in Carolina’s Fundamental Constitutions. It enables the reader to view, and judge, the relevant evidence. The author concludes, and invites the reader to conclude, that Armitage’s main claims lack foundation in the manuscript evidence. That evidence instead points towards the legal power of those who owned Carolina, the Lords Proprietors, and to the crown, which granted Carolina’s charter, and to the logic of a different theory of government, patriarchalism, for the rationale behind both slavery and absolutism. The central ideas behind slavery and colonization were epitomized, as Locke understood, by Sir Robert Filmer, who wrote the book to which Locke responded in his Two Treatises of Government. Filmer’s ally, Sir Henry Spelman, like Filmer a deeply committed royalist who believed in the king’s unlimited prerogatives, composed the original 1629 Carolina charter that shaped the Fundamental Constitutions. Misattributing the authorship of particular clauses to Locke is a symptom of a larger failure to distinguish the impact of momentous debates over authority and race in the seventeenth century. Locke’s theories did, in practice as well as principle, reject the theory of domination put forward by Filmer, and argued instead for human rights and democracy that were inclusive and capacious. The manuscript evidence has the potential to reshape how modern democratic theory is understood in the present.